The Confirmatory Factor Analysis on Factors Influencing Decision to Use Medical Tourism Services from CLMV Countries in Thai-Laos Border Area, Nongkhai and Udon Thani Provinces - Srirak, Chainarong (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2021)
The purposes of this research were to: 1) study medical tourism behaviors of CLMV tourists in Thai-Laos border, Nongkhai and Udon Thani provinces; and2) conduct confirmatory factor analysis on factors influencing decision to use medical tourism services of CLMV tourists in Thai-Laos border, Nongkhai and Udon Thani provinces. This survey research used questionnaire tool to compile data from 400 samples of tourists. The accidental random sampling was used for this study. The descriptive statistics were used for data analysis, which consisted of frequency, percentage, arithmetic mean, and standard deviation. The inferential statistics were the congruence indexes, which consisted of Chi-square (c2), CMIN/df, RMSEA, RMR AGFI and GFI. The results found that the majority of medical tourists from CLMV countries were business owners; female; and cross border to receive services for special diagnosis, health checkup, ophthalmology,obstetrics, gynecology and delivery, cardiology, dentistry, surgery and health restoration, respectively. The model of factors were goodness of fit with empirical data with statistical Chi-Square = 11.42, df = 8, P = 0.11, GFI = 0.99, AGFI = 0.89, RMR= 0.0025, RMSEA= 0.0034. The factors in the model were able to explainvariance of decision to use medical service 64%(R2 = .64). The factor weights were ranked as follows: marketing promotion factor (β = 0.83); personal need responses factor (β = 0.74); service quality and pricefactor(R2 = 0.69); place and accessfactor (β = 0.58); facilitiesfactor (β = 0.53); and tourism resources/ attractionsfactor (β = 0.41), respectively. The results of study can be benefits for strategic formulation, development and promotion for medical tourism services towards tourists of CLMV countries in Thai-Laos Border Area.